Dual-Polarization Self-Coherent Transceivers for Free Space Optical Communications in the Presence of Atmospheric Turbulence - Yeganeh Nasr; Shiva Kumar; Jiaoyang Bi; Mahdi Naghshvarianjahromi; M. Jamal Deen (IEEE Access)
The self-coherent scheme offers significant advantages for free-space optical (FSO) communications, particularly due to its higher oscillator-signal mixing efficiency compared to conventional coherent schemes. This paper presents an analysis and simulation results of an FSO system utilizing the dual-polarization (DP) self-coherent scheme, where independent quadrature amplitude modulation (QAM) data is transmitted for each polarization. Atmospheric turbulence, however, introduces random polarization rotation and polarization-dependent phase shifts, which cause the effective channel matrix to become singular at certain angles. This leads to an increased bit error rate (BER) in conventional systems that use two photodetectors (PDs). To address this issue, we propose a novel detection scheme using three PDs. This study evaluates the performance of long-haul FSO transceivers, comparing the DP self-coherent scheme with the conventional coherent scheme under a variety of conditions, including satellite-to-ground, ground-to-satellite, and satellite-to-satellite links. The analysis spans different levels of atmospheric turbulence, ranging from weak to moderate to strong, providing a comprehensive assessment of transmission efficacy.